PROSTATE SPECIFIC ANTIGEN LEVEL FOLLOWING TRANSURETHRAL RESECTION OF THE PROSTATE - Aritonang, Johannes; Ali, Zulfikar (Indonesian Journal of Urology, 2020)
Objective: To evaluate the correlation of the weight of the resected prostate with the reduction of the PSA level. Material & methods: This is a prospective study of all BPH patients undergoing TURP procedure in Kardinah Hospital, Tegal, with a timeframe of April–June 2018. Patients consumed α-blocker and 5-α reductase inhibitor medication before the procedure were eliminated from the study. The data collected were the estimated prostate weight calculated using transabdominal ultrasonography (TAUS) of the prostate, PSA level before and after the procedure, and the calculated weight of the resected prostate. The resected tissues of the prostate were examined by an anatomy pathologist and the PSA level will be examined at 1, 14, and 30 days after the surgery. Data was analyzed using repeated measure ANOVA with SPSS version 23.0. Results: We included 35 cases of prostate enlargement in our center. 2.8% of the patients didn’t undergo definitive surgical procedure due to be postponed with various reasons. The patients mean age is 64.2 ± 8.26 with average BMI is 21.8 ± 3.56kg/m2. The median value of the prostate volume is 43.8 mL. The median preoperative PSA level was 8.7 ng/dL, while the median value of the 1st day, 14th days, and 30th days post-operative PSA level were17.67 ng/dL, 6.93 ng/dL, and 3.2 ng/dL, respectively, with significant reduction of PSA level (p<0.001). Conclusion: PSA level post-TURP shows a significant decrease. Every milliliters (mL) prostatic tissue resected could reduce the PSA level for 0.11 ng/mL. This calculation could further be used to predict how much tissue needed to resect, to treat the symptoms, and obtain normal PSA level. In addition, further research is needed, especially with larger sample size and longer follow up period to confirm these findings.